Pengaruh Sikap Belajar Terhadap Hasil Belajar Siswa Kelas XI IPS SMA Negeri 1 Jakarta Pada Mata Pelajaran Geografi - Rahman, Dinda Aulia; Mataburu, Ilham Badaruddin; Kusumawati, Lia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research explores the correlation between learning attitudes and learning outcomes in Geography among 11th-grade students in SMA Negeri 1 Jakarta. The study adopted a correlational research type and employed a saturation sampling technique, with all 11th-grade Social Science (IPS) students at SMA Negeri 1 Jakarta as the population. The variables were learning attitude as the independent variable and learning outcome as the dependent variable. Data on learning attitudes were collected using a questionnaire, while data on learning outcomes were based on Mid-Semester Exam (PTS) scores. The hypotheses were tested using a linear regression analysis. The findings indicated a significant influence of learning attitudes on the learning outcomes of 11th-grade Social Science students in Geography at SMA Negeri 1 Jakarta. The linear regression analysis produced a simple linear regression equation: Y = 64.330 + 0.193X. It implied that fostering positive learning attitudes can improve the learning outcomes of students.